Competitive biosorption of pb (ii) and ni (ii) onto newly synthesized spongy thiourea modified spentgrated coconut / Muhammad Ikram Mohd Apdi@normi - Mohd Apdi@normi, Muhammad Ikram (Faculty of Applied Sciences, 2017)
The waste from spent-grated coconut was used and modified as new biosorbent to investigate the biosorption of Pb (ii) and Ni (ii). Initially, SGC was treated with hexane and followed by thiourea to form TSGC. This biosorbent were characterized by FTIR, pHslurry and pHzpc. The experimental equilibrium adsorption data were analyzed by two model and two isotherm- Pseudo-first order model, Pseudo-second order model, Langmuir isotherm and Freundlich isotherm. Among these, only Freundlich isotherm was fitted with both Pb (lI) and Ni (II) as it correlation coefficients (R2) close to to unity. For Pseudo-first order model, only Pb (II) ions was fit with it. For Pseudo-second order model, only Ni (ii) was fit it.